Nonlinear Structural Acoustic Control with Shunt Circuit Governed by a Soft-Computing Algorithm - Sebastian KURCZYK; Marek PAWEŁCZYK (Archives of Acoustics, 2018)
Noise control has gained a lot of attention recently. However, presence of nonlinearities in signal paths for some applications can cause significant difficulties in the operation of control algorithms. In particular, this problem is common in structural noise control, which uses a piezoelectric shunt circuit. Not only vibrating structures may exhibit nonlinear characteristics, but also piezoelectric actuators.